Currículos da escola brasileira: elementos para uma análise discursiva - Marildes Marinho (Universidade do Minho, 2007)
This text is organised according to some theoretical-methodological basic principles in order to give support to the analyses of educational texts from a discursive perspective. It takes as its object the Portuguese Language Curriculum and the National Curricular Parameters published in Brazil in the last two decades of the 20th century. By placing discourse in the field of curriculum studies, the curriculum is analysed through the author/readers representations inscribed in its discourse strategies. Besides the pedagogical innovations that these documents propose they also introduce a new rhetoric in the curricular genre, emphasising its own features in connection to the scientific discourses: linguistics and educational sciences.